Book reviews - Redactie KITLV (NWIG, 2011)
Create Dangerously: The Immigrant Artist at Work, by Edwidge Danticat (reviewed by Colin Dayan)

Gordon K. Lewis on Race, Class and Ideology in the Caribbean, edited by Anthony P. Maingot (reviewed by Bridget Brereton)

Freedom and Constraint in Caribbean Migration and Diaspora, edited by Elizabeth Thomas-Hope (reviewed by Mary Chamberlain)

Black Europe and the African Diaspora, edited by Darlene Clark Hine, Trica Danielle Keaton & Stephen Small (reviewed by Gert Oostindie)

Caribbean Middlebrow: Leisure Culture and the Middle Class, by Belinda E dmondson (reviewed by Karla Slocum)

Global Change and Caribbean Vulnerability: Environment, Economy and Society at Risk, edited by Duncan McGregor, David Dodman & David Barker (reviewed by Bonham C. Richardson)

Encountering Revolution: Haiti and the Making of the Early Republic, by Ashli White (reviewed by Matt Clavin)

Red and Black in Haiti: Radicalism, Conflict, and Political Change, 1934-1957, by Matthew J. Smith (reviewed by Robert Fatton Jr.)

Cuba in the American Imagination: Metaphor and the Imperial Ethos, by Louis A. Pérez Jr. (reviewed by Camillia Cowling)

Seeds of Insurrection: Domination and Resistance on Western Cuban Plantations, 1808-1848, by Manuel Barcia (reviewed by Matt D. Childs)

Epidemic Invasions: Yellow Fever and the Limits of Cuban Independence, 1878-1930, by Mariola Espinosa (reviewed by Cruz Maria Nazario)

The Cuban Connection: Drug Trafficking, Smuggling, and Gambling in Cuba from the 1920s to the Revolution, by Eduardo Sáenz Rovner (reviewed by Ivelaw
Lloyd Griffith)

Before Fidel: The Cuba I Remember, by Francisco José Moreno, and The Boys from Dolores: Fidel Castro’s Schoolmates from Revolution to Exile, by Patrick Symmes (reviewed by Pedro Pérez Sarduy)

Lam, by Jacques Leenhardt & Jean-Louis Paudrat (reviewed by Sally Price)

Healing Dramas: Divination and Magic in Modern Puerto Rico, by Raquel Romberg (reviewed by Grant Jewell Rich)

Puerto Rican Citizen: History and Political Identity in Twentieth-Century New York City, by Lorrin Thomas (reviewed by Jorge Duany)

Livestock, Sugar and Slavery: Contested Terrain in Colonial Jamaica, by Verene A. Shepherd (reviewed by Justin Roberts)

Daddy Sharpe: A Narrative of the Life and Adventures of Samuel Sharpe, a West Indian Slave Written by Himself, 1832, by Fred W. Kennedy (reviewed by Gad Heuman)

Becoming Rasta: Origins of Rastafari Identity in Jamaica, by Charles Price (reviewed by Jahlani A. Niaah)

Reggaeton, edited by Raquel Z. Rivera, Wayne Marshall & Deborah Pacini Hernandez (reviewed by Alexandrine Boudreault-Fournier)

Carriacou String Band Serenade: Performing Identity in the Eastern Caribbean, by Rebecca S. Miller (reviewed by Nanette de Jong)

Caribbean Visionary: A.R.F. Webber and the Making of the Guyanese Nation, by Selwyn R. Cudjoe (reviewed by Clem Seecharan)

Guyana Diaries: Women’s Lives Across Difference, by Kimberely D. Nettles (reviewed by D. Alissa Trotz)

Writers of the Caribbean Diaspora: Shifting Homelands, Travelling Identities, edited by Jasbir Jain & Supriya Agarwal (reviewed by Joy Mahabir)

Queen of the Virgins: Pageantry and Black Womanhood in the Caribbean, by M. Cynthia Oliver (reviewed by Tami Navarro)

Notions of Identity, Diaspora, and Gender in Caribbean Women’s Writing, by Brinda Mehta (reviewed by Marie-Hélène Laforest)

Authority and Authorship in V.S. Naipaul, by Imraan Coovadia (reviewed by A shley Tellis)

Typo/Topo/Poéthique sur Frankétienne, by Jean Jonassaint (reviewed by Martin Munro)

Creoles in Education: An Appraisal of Current Programs and Projects, edited by Bettina Migge, Isabelle Léglise & Angela Bartens (reviewed by Jeff Siegel)

Material Culture in Anglo-America: Regional Identity and Urbanity in the Tidewater, Lowcountry, and Caribbean, edited by David S. Shields (reviewed by Susan Kern)

Tibes: People, Power, and Ritual at the Center of the Cosmos, edited by L. Antonio Curet & Lisa M. Stringer (reviewed by Frederick H. Smith)